Schistosoma mansoni and HIV infection in a Ugandan population with high HIV and helminth prevalence. Issue 9 (1st June 2015) - Sanya, Richard E.; Muhangi, Lawrence; Nampijja, Margaret; Nannozi, Victoria; Nakawungu, Prossy Kabuubi; Abayo, Elson; Webb, Emily L.; Elliott, Alison M.; the LaVIISWA study team; Nampijja, Margaret; Sanya, Richard; Nerima, Barbara; et al.
Abstract Objectives Recent reports suggest that Schistosoma infection may increase the risk of acquiring human immunodeficiency virus (HIV). We used data from a large cross‐sectional study to investigate whether Schistosoma mansoni infection is associated with increased HIV prevalence. Methods We conducted a household survey of residents in island fishing communities in Mukono district, Uganda, between October 2012 and July 2013. HIV status was assessed using rapid test kits. Kato‐Katz (KK) stool tests and urine‐circulating cathodic antigen (CCA) were used to test for Schistosoma infection. Multivariable logistic regression, allowing for the survey design, was used to investigate the association between S. mansoni infection and HIV infection. Results Data from 1412 participants aged 13 years and older were analysed (mean age 30.3 years, 45% female). The prevalence of HIV was 17.3%. Using the stool Kato‐Katz technique on a single sample, S. mansoni infection was detected in 57.2% (719/1257) of participants; urine CCA was positive in 73.8% (478/650) of those tested. S. mansoni infection was not associated with HIV infection. [KK (aOR = 1.04; 95% CI: 0.74–1.47, P = 0.81), CCA (aOR = 1.53; 95% CI: 0.78–3.00, P = 0.19)]. The median S. mansoni egg count per gram was lower in the HIV‐positive participants (P = 0.005). Conclusions These results add to the evidence that S. mansoni has little effect on HIV transmission, but may influence egg excretion.